Nonlinear delay differential equations involving population growth - Y. Lenbury (2018)
Conditions are given on the function f, such that population χ(t) given by#x003C7;(t) = μχ(t) + f(χ(t - τ)), becomes extinct or remains globally stable. Our theorems are shown to be applicable to the Nicholson's model of blowflies and the population dynamics of baleen whales. In some of these cases, the function f is unimodal rather than monotone. © 2004 Elsevier Ltd. All rights reserved.